2021
DOI: 10.1155/2021/6580458
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Risk Factors for Heart Disease: A Challenge to the Ethnopharmacological Use of Croton urucurana Baill.

Abstract: Croton urucurana Baill. is a native Brazilian tree, popularly known as “sangra-d’água” or “sangue-de-dragão,” based on the red resinous sap of the trunk. Its use has been transmitted through generations based on popular tradition that attributes analgesic, anti-inflammatory, and cardioprotective properties to the tree. However, its cardioprotective effects have not yet been scientifically investigated. Thus, the present study investigated the pharmacological response to an ethanol-soluble fraction from the lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Despite other studies that indicated the presence of various condensed tannins in C. urucurana , we observed a single peak at m/z 579.149 (peak 10) in the present extract, with a main fragment at m/z 289.070, which was characteristic of (epi)catechin-(epi)catechin, as previously described ( Souza et al, 2008a ; Casao et al, 2020 ). Peak 12 at m/z 291.0862 was identified as catechin, confirmed by comparison with an authentic standard ( Zago et al, 2021 ).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Despite other studies that indicated the presence of various condensed tannins in C. urucurana , we observed a single peak at m/z 579.149 (peak 10) in the present extract, with a main fragment at m/z 289.070, which was characteristic of (epi)catechin-(epi)catechin, as previously described ( Souza et al, 2008a ; Casao et al, 2020 ). Peak 12 at m/z 291.0862 was identified as catechin, confirmed by comparison with an authentic standard ( Zago et al, 2021 ).…”
Section: Resultsmentioning
confidence: 77%
“…Thus, we used the 30 mg/kg dose, a 10-times higher dose (i.e., 300 mg/kg), and an intermediate dose on a logarithmic scale (100 mg/kg; Coelho et al, 2019 ). Electrocardiograms, heart rate, and blood pressure in these normotensive and hypertensive rats were described in a previous study by our group ( Zago et al, 2021 ).…”
Section: Methodsmentioning
confidence: 95%
“…Hypertension, dyslipidemia, unhealthy nutrition, and hormonal alterations are known to strongly correlate with worse cardiovascular outcomes, either in the presence or absence of CVD [10]. Although CVD is a global health problem, animal models that combine mul-tiple cardiovascular risk factors are scarce [11]. The present study developed an effective animal model that mimics human conditions of multiple cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Animals were randomly divided into experimental groups, with 8 rats per group. Te selection of this group size was based on previous results from similar experimental protocols and adhered to the 3R principles (reduce, refne, and replace) [12][13][14][27][28][29]. Weights were assessed on a weekly basis using an analytical balance.…”
Section: Animals Te Research Model Involved the Development Of Malementioning
confidence: 99%